2015
DOI: 10.18619/2072-9146-2015-3-4-104-107
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Selenium Accumulation by Plants

Abstract: Гормональное регулирование представляет собой уникальный механизм, определяющий рост и развитие живого организма. В обзоре рассмотрены факты взаимосвязи гормонального статуса растений не аккумуляторов и гипераккумуляторов селена с уровнями накопления микроэлемен-та, явление стимулирования накопления и перераспределения селена под действием фитогор-монов, видовые и сортовые особенности воздействия фитогормонов, а также влияние пола растения на уровни накопления микроэлемента. Приводятся данные гормонального рег… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The content of Se in the organism is also a subject of hormonal regulation, however, mechanisms of such regulation are well detailed in mammals 15,16 , and only partially described in plants. The authors demonstrated the effect of epibrasinolideles, heteroauxin, and gibberellin on accumulation of microelements in plant organs.…”
Section: Resultsmentioning
confidence: 99%
“…The content of Se in the organism is also a subject of hormonal regulation, however, mechanisms of such regulation are well detailed in mammals 15,16 , and only partially described in plants. The authors demonstrated the effect of epibrasinolideles, heteroauxin, and gibberellin on accumulation of microelements in plant organs.…”
Section: Resultsmentioning
confidence: 99%
“…Lotus demonstrated the opposite trend, with a significantly more intense pulp Se increase compared to the peel data (Figure 4). The beneficial effect of Se in improving plant tolerance to abiotic stresses is largely connected with its antioxidant properties [58] and its ability to regulate the biosynthesis of phytohormones [59,60], thus affecting all biochemical reactions of the plant organism.…”
Section: Elemental Compositionmentioning
confidence: 99%
“…Внекорневые подкормки считаются высокопродуктивным приемом земледелия из-за высокой эффективности при незначительных затратах, а также возможности совмещения их с обработками растений от вредителей и болезней. Листовая подкормка также часто используются, как срочная мера в случае дефицита отдельных элементов питания в растениях [6,7]. Отмечается, что эффект от некорневой обработки тем выше, чем беднее почва питательным элементом, вносимым через листья, что является благоприятным фактором для обогащения растений селеном, учитывая дефицит почв России в этом элементе.…”
Section: Introductionunclassified